Stress, Affect Regulation and Attachment of People With Sensory and Intellectual Disabilities - de Vaan, Gitta; Vervloed, Mathijs P. J.; Knoors, Harry; Verhoeven, Ludo (Frontiers in Education, 2020)
Background In persons with combined intellectual and sensory disabilities, mood disorders, stress reactions and attachment problems are more prevalent. This study assessed the presence of these problems within this target population and the effects of an additional Autism Spectrum Disorder (ASD). Method Participants were 60 individuals with combined intellectual and sensory disabilities, all participants had visual impairments, 16 were deafblind. ASD was assessed with Observation of Autism in people with Sensory and Intellectual Disabilities. Additionally the Anxiety, Depression and Mood Scale, The list of Disturbed Attachment Behaviours and the Stress Survey Schedule were used. Results Almost every participant showed signs of a disturbed attachment. Stress and mood disorders were not prevalent. An additional ASD resulted in more disturbed attachment, manic and hyperactive behaviour and social avoidance. Conclusions Only for disturbed attachment a relatively high prevalence was found. The presence of ASD sometimes led to a different profile of the assessed problems.